ENHANCING CALLUS FORMATION IN TAPAKTUAN PATCHOULI THROUGH IN VITRO OPTIMIZED COMBINATIONS OF PGR - Alya Munira; Khairan Khairan; Sreeramanan Subramaniam; Essy Harnelly (SEAMEO BIOTROP, 2025)
Article Highlight- Different varieties of Patchouli exhibited different growth pattern as well as in vitro culture- In order to induce callus, it has been determined that the combination of regulators is necessary.- Benzylaminopurine has been identified as a potential regulator that could be used to further develop the patchouli callus of Tapak Tuan. Abstract: Patchouli is known for its highly demanded essential oil. The Patchouli Tapaktuan variety is the most widely cultivated by local farmers in Aceh due to its high oil yield. Currently, the study and propagation of patchouli through a biotechnological approach is being developed, one of which is in vitro culture method. In this method, suitable Plant Growth Regulators (PGR) are being observed to enhance the growth of the explant. PGRs are synthetic compounds that are added to media in plant tissue culture to stimulate plant growth. This study aimed to analyze and optimize the effect of benzylaminopurine (BAP), thidiazuron (TDZ) combined with Naphthaleneacetic acid (NAA) on the growth of Tapaktuan patchouli leaf callus. This study was carried out by using a completely randomized design with seven treatments. Each treatment was replicated four times and each replicate contained three explants. The concentrations used were BAP 0.75 mg/L, TDZ 1 mg/L, and NAA in the 0.25 - 0.75 mg/L range. According to this study, combining BAP and NAA was the most effective for inducing callus in Tapaktuan patchouli leaves. The combination of BAP 0.75 mg/L + NAA 0.5 mg/L (treatment A2) was the most effective for inducing callus formation. This treatment resulted in the quickest callus development, the highest percentage of callus formation, and the largest callus diameter. Explants cultured with BAP produced a greenish-yellow callus having the potential for organogenesis culture, which could produce shoots having the ability for producing mass plantlets.